Urban Green Spaces and People’s Well-being: the Limassol District Analysis - Magou, Afroditi (My University, 2025)
Rapid urbanization is challenging the quality of life of people living in urban environment, by consuming available Urban Green Spaces (UGS), minimizing their quantity. UGS are widely acknowledged for their ecological and social benefits. Yet, a subjective well-being (SWB) analysis might enrich context-specific research of how UGS influence residents’ well-being. As the relevant literature indicates, a gap exists in this topic when it comes to Cyprus and more specifically Limassol District. Hence, this thesis is trying to identify the relationship between the UGS, their spatial characteristics and the residents’ SWB in Limassol District, Cyprus. It employs a mixed-methods approach, combining Geographic Information System (GIS) analysis to objectively quantify UGS attributes (e.g., quantity, quality, accessibility) with a structured survey designed to gather data on SWB levels, UGS perceptions, and perceived climate change impacts. The results can eventually guide data-driven urban planning and assist in the development of more climate and resident resilient municipalities.
Keywords: Urban Green Spaces; Subjective Well-being; GIS; Urban Planning; Climate Adaptation